2012
DOI: 10.1177/004005991204500102
|View full text |Cite
|
Sign up to set email alerts
|

Do it Yourself: Video Self-Modeling Made Easy

Abstract: Elaine, a tutor, and Carlo, a fourth-grader, sit together at a table with a laptop. They discuss the book that Carlo is about to read, which Carlo chose from a set of preselected books at his instructional level. Elaine and Carlo discuss the cover of the book before starting to read, then they read a few pages in unison. After 2 minutes of unison reading, Elaine reaches over to the laptop, hits a button, and starts recording the rest of their tutoring session on video When Carlo first sat down at the table, El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…, communication disorders such as selective mutism and stuttering (Bray & Kehle, 2001; Kehle, Bray, Byer-Alcorace, Theodore, & Kovac, 2012), learning disabilities (Prater, Carter, Hitchcock, & Dowrick, 2012;Rao et al, 2012), physical disabilities (Dowrick & Raeburn, 1995), depression (Kahn, Kehle, Jenson, & Clark, 1990), and attention deficit and hyperactivity disorders (ADHD; Woltersdorf, 1992). Within the past 6 or 7 years, researchers have found this technique to be particularly effective for children with autism spectrum disorder (Buggey et al, 2011;Plavnick, Sam, Hume, & Odom, 2013).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…, communication disorders such as selective mutism and stuttering (Bray & Kehle, 2001; Kehle, Bray, Byer-Alcorace, Theodore, & Kovac, 2012), learning disabilities (Prater, Carter, Hitchcock, & Dowrick, 2012;Rao et al, 2012), physical disabilities (Dowrick & Raeburn, 1995), depression (Kahn, Kehle, Jenson, & Clark, 1990), and attention deficit and hyperactivity disorders (ADHD; Woltersdorf, 1992). Within the past 6 or 7 years, researchers have found this technique to be particularly effective for children with autism spectrum disorder (Buggey et al, 2011;Plavnick, Sam, Hume, & Odom, 2013).…”
Section: )mentioning
confidence: 99%
“…An outgrowth of this technology has been video self-modeling (VSM), which has been effective for teaching students academic skills such as reading and math (Dowrick, Kim-Rupnow, & Power, 2006; Rao, Hitchcock, Boisvert, Kilpatrick, & Corbiell, 2012), promoting social initiations and engagement (Bellini, Akullian, & Hopf, 2007; Buggey, Hoomes, Sherberger, & Williams, 2011), and learning self-help skills (Norman, Collins, & Schuster, 2001; Sigafoos, O’Reilly, & Cannella, 2005). VSM has also been effective across a wide variety of disabilities including, but not limited to, emotional and behavioral disorders (Losinski, Wiseman, White, & Balluch, 2016; O’Reilly et al, 2005), intellectual disabilities (Norman et al, 2001; Sigafoos et al, 2005), communication disorders such as selective mutism and stuttering (Bray & Kehle, 2001; Kehle, Bray, Byer-Alcorace, Theodore, & Kovac, 2012), learning disabilities (Prater, Carter, Hitchcock, & Dowrick, 2012; Rao et al, 2012), physical disabilities (Dowrick & Raeburn, 1995), depression (Kahn, Kehle, Jenson, & Clark, 1990), and attention deficit and hyperactivity disorders (ADHD; Woltersdorf, 1992). Within the past 6 or 7 years, researchers have found this technique to be particularly effective for children with autism spectrum disorder (Buggey et al, 2011; Plavnick, Sam, Hume, & Odom, 2013).…”
mentioning
confidence: 99%
“…Unlike findings in literacy (Rao et al, 2012; Gillies, 2013), autism (Bellini et al, 2007), cerebral palsy (Dowrick, 1976) and other behavioral sciences (Dowrick, 2012), sport movement studies have indicated mixed results in support of the learning efficacy of this method (e.g., Starek and McCullagh, 1999; Law and Ste-Marie, 2005; Feltz et al, 2008). …”
Section: Introductionmentioning
confidence: 92%
“…enough interesting components to maintain the child's attention across a 2-to 3-minute video (Buggey, 2009;Hitchcock et al, 2003;Rao et al, 2012); however, too many extraneous details may be distracting. This is especially true for children with ASD, who can become engrossed in a small detail within the movie and miss the larger goal of observing the positive behavior or skill.…”
Section: Momentary Time Samplingmentioning
confidence: 99%